Guía Metodológica para la Gestión de Proyectos Pequeños en el Departamento de Planillas de Recursos Humanos de un Centro de Servicios - Campillo-Córdoba, Sebastián; Castro-Jiménez, María (Instituto Tecnológico de Costa Rica, 2013)
The Payroll Department joined a Global Service Center becoming responsible for processes from 10 countries within the Americas. The interrelated critical processes were handled independently, not only generating ineffective and inefficient services, but communication gaps as well. Applied Research was done in four phases: Phase 1, the project management capabilities were exposed. In Phase 2, the set of critical processes to be addressed with a focus on small projects were identified. For Phase 3, a methodological guide was created to carry out the projects based on the PMBOK ® and PRINCE2 ™. Finally in Phase 4, an implementation plan was defined for the proposed guide. The capabilities analysis, in Project Management, shows that the department leaders have the most hours of approved courses in a year and Payroll has led 35 projects. 17 critical processes were identified to be addressed with six small projects using the proposed methodological guide that promotes a culture of standardization and proactive behavior. The solution can be extended to other regions of Asia and Europe. It is recommended to start with a pilot program that incorporates an individual in charge of performing direct observations; this would facilitate the identification of waste on areas for improvement based on Lean culture.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2013.
Keywords: Gestión de proyectos; Estandarización; Planificación; Recursos humanos; Servicios; Monitoreo